2012
DOI: 10.1016/j.eururo.2012.01.037
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Automated Platform for Quantifying the Extent of Skeletal Tumour Involvement in Prostate Cancer Patients Using the Bone Scan Index

Abstract: Background There is little consensus on a standard approach to analysing bone scan images. The Bone Scan Index (BSI) is predictive of survival in patients with progressive prostate cancer (PCa), but the popularity of this metric is hampered by the tedium of the manual calculation. Objective Develop a fully automated method of quantifying the BSI and determining the clinical value of automated BSI measurements beyond conventional clinical and pathologic features. Design, setting, and participants We conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
180
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 165 publications
(199 citation statements)
references
References 14 publications
11
180
1
Order By: Relevance
“…The BS index (BSI) is the percentage of bone mass involved by lesions on BS that uses a historical standard for overall bone mass. 16,17 However, the applicability of BS progression using PCWG criteria or BSI to other classes of novel agents is unclear. Indeed, despite an improvement in BSI and radiographic PFS (which mostly consisted of BS progression) with tasquinimod (an investigational antiangiogenic and immune-modulating drug), this agent did not yield an extension of OS in a phase III trial.…”
Section: Discussionmentioning
confidence: 99%
“…The BS index (BSI) is the percentage of bone mass involved by lesions on BS that uses a historical standard for overall bone mass. 16,17 However, the applicability of BS progression using PCWG criteria or BSI to other classes of novel agents is unclear. Indeed, despite an improvement in BSI and radiographic PFS (which mostly consisted of BS progression) with tasquinimod (an investigational antiangiogenic and immune-modulating drug), this agent did not yield an extension of OS in a phase III trial.…”
Section: Discussionmentioning
confidence: 99%
“…Automated methods for interpreting bone scans and calculating BSI are under development. Ulmet et al developed computer-assisted BSI measure and reported that BSI is a valuable metric for estimating metastatic burden in patients with advanced prostate cancer (Ulmert et al 2012). The same team also reported that automated BSI calculation, like its manual counterpart, is a valuable clinical parameter in patients with progressive prostate cancer.…”
Section: Novel Imaging Biomarkersmentioning
confidence: 94%
“…Automated quantitative determination of bone metastases using the bone scan index may have diagnostic, prognostic and predictive value in patients with mCRPC, but it is still subject to validation [73]. Markers of tumor activity in bone as N-telopeptide and bone AP (reflecting osteolytic and osteoblastic activity) have been shown to be prognostic and survival markers [74][75][76][77].…”
Section: Molecular Biomarkersmentioning
confidence: 98%